2021
DOI: 10.3906/tar-2102-12
|View full text |Cite
|
Sign up to set email alerts
|

The first report about genetic diversity analysis among endemic wild rhubarb (Rheum ribes L.) populations through iPBS markers

Abstract: Approximately 30% of plant species of Turkey, which is among the richest countries in terms of biodiversity, has been endemic. Wild rhubarb (Rheum ribes L.) is a wild vegetable grows especially in the eastern region of Turkey and is an endemic species.In this study, genetic relationships among 80 wild rhubarb genotypes collected from some regions of Lake Van Basin, which are in the distribution area, were tried to be determined by iPBS marker system. At the same time, a commercial variety of R. rhabarbarum, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Estimating genetic diversity is considered a precursor for crop improvement, giving relevant data for selections and breeding programs ( Pal et al, 2016 ; Erdinc et al, 2021 ; Hasanbegovic et al, 2021 ). Furthermore, it is helping researchers develop new cultivars with desired traits such as yield and quality; genetic resources facilitate the introgression of novel traits required in the production of plants under different climates ( Holmes et al, 2019 ; Park et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating genetic diversity is considered a precursor for crop improvement, giving relevant data for selections and breeding programs ( Pal et al, 2016 ; Erdinc et al, 2021 ; Hasanbegovic et al, 2021 ). Furthermore, it is helping researchers develop new cultivars with desired traits such as yield and quality; genetic resources facilitate the introgression of novel traits required in the production of plants under different climates ( Holmes et al, 2019 ; Park et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Medicinal plants are affordable, simple to use, and have fewer adverse effects than current synthetic drugs [ 8 ]. Numerous studies show the fascinating benefits of plant-based medicines used in complementary, alternative, and traditional medicine to cure human ailments [ [9] , [10] , [11] ]. A report from the World Health Organization (WHO) has also recently reported that nearly three-quarters of the global population is currently using herbs and herbal remedies for therapeutic purposes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among plants, the study of medicinal plants has gained worldwide attention in recent years. A substantial amount of research demonstrates the intriguing potential of medicinal plants employed in traditional, complementary, and alternative methods of treating human ailments ( Fitzgerald et al, 2020 ; Erdinc et al, 2021 ; Tamer et al, 2021 ). The investigation of medicinal plants as a unique source of enzyme inhibitors, natural antioxidant components, and treatments for a variety of common illnesses has attracted considerable interest ( Phumthum et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%